Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction